1991
DOI: 10.1128/mcb.11.6.3105
|View full text |Cite
|
Sign up to set email alerts
|

Translation initiation factor 5A and its hypusine modification are essential for cell viability in the yeast Saccharomyces cerevisiae.

Abstract: Translation initiation factor eIF-5A (previously named eIF-4D) is a highly conserved protein that promotes formation of the first peptide bond. One of its lysine residues is modified by spermidine to form hypusine, a posttranslational modification unique to eIF-5A. To elucidate the function of eIF-5A and determine the role of its hypusine modification, the cDNA encoding human eIF-5A was used as a probe to identify and clone the corresponding genes from the yeast Saccharomyces cerevisiae. Two genes named TIFS1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
264
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(276 citation statements)
references
References 44 publications
(22 reference statements)
10
264
1
1
Order By: Relevance
“…In the early 1980s, Myung Park and collaborators demonstrated that the polyamine spermidine was the essential substrate for the posttranslational modification of the putative eukaryotic translation inhibition factor 5A (eIF5A) 103 . Subsequent studies have shown that the Saccharomyces cerevisiae equivalent of eIF5A is an essential gene in this yeast 104 , but is not essential for general protein synthesis 105,106 . Rather, eIF5A seems to be involved in the processing of specific RNAs 107,108 .…”
Section: Box 2 | Mechanisms Of Polyamine-dependent Gene Expressionmentioning
confidence: 99%
“…In the early 1980s, Myung Park and collaborators demonstrated that the polyamine spermidine was the essential substrate for the posttranslational modification of the putative eukaryotic translation inhibition factor 5A (eIF5A) 103 . Subsequent studies have shown that the Saccharomyces cerevisiae equivalent of eIF5A is an essential gene in this yeast 104 , but is not essential for general protein synthesis 105,106 . Rather, eIF5A seems to be involved in the processing of specific RNAs 107,108 .…”
Section: Box 2 | Mechanisms Of Polyamine-dependent Gene Expressionmentioning
confidence: 99%
“…Knock-out of either the eif5a or dhs gene is fatal in yeast. 2,3,14 Two eIF5A isoforms, eIF5A1 and eIF5A2, occur in humans and have 84% identity in their amino acid sequence. [15][16][17][18] The eif5a1 gene is ubiquitously expressed, whereas eif5a2 is highly expressed in the testis and at moderate levels in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of deoxyhypusine synthase activity by chemicals [4] or by limiting the level of the substrate spermidine [5] arrests the growth of eukaryotic cells, suggesting that this enzyme may play a pivotal role in cell growth. It has been shown by mutational analysis that preservation of the site of hypusination of eIF-5A (Lys 51 in the yeast precursor) is vital for the factor's function(s) [6]. Yeast contains two forms of 5A, designated eIF-5Aa and eIF-5Ab, derived from two distinct genes reciprocally regulated by oxygen [6].…”
Section: Introductionmentioning
confidence: 99%